Economy of knowledge: methodology for the development of agrotourism - González Sánchez, Angélica María (2018)
The transfer of knowledge allows an individual to become an innovator, encouraging the increase of entrepreneurship and employment. The objective of the research is to analyze the methodological context of the knowledge economy in the development of agrotourism; for which a mixed method was used framed in two approaches: documentary and exploratory, taking as reference the index of knowledge economy proposed by the World Bank. As a result, it was concluded that the foundation of theories and meanings of agrotourism, sustainable rural development, entrepreneurial culture, employability and knowledge-based economy contributed to the development of a program of tourist dynamism, which generated the development of agrotourism ventures and increased employability. which promoted the increase of an inclusive economy with respect to the economically active population of the parish of the Peninsula of Ambato canton of Tungurahua province.